Nurse educators’ challenges of problem-based learning implementation at Ethiopian public universities: A phenomenological qualitative study - Getachew Nigussie Bolado; Bizuayehu Atinafu Ataro; Tamirat Ersino Kebamo; Agumas Shibabaw Ayana; Worku Mimani Minuta (PLoS ONE, 2025)
Background Nursing students are the upcoming healthcare workforce who learn to face the reality of their roles and work in clinical practice, knowing all aspects of patient care and contributing their knowledge, attitude, and practice to the healthcare system in the future. Problem-based learning is one of the strategies to identify and encourage their theoretical, practical, and clinical thinking abilities. Still, its implementation is hindered by different shortcomings in developing countries, especially in Ethiopia. Objective To explore the nurse educators’ challenges with problem-based learning implementation at Ethiopian public universities, 2023. Method A phenomenological qualitative study design approach was used. Eighteen nurse educators were selected purposively from ten universities to explore the challenges they encountered while implementing problem-based learning. Data were collected using in-depth interviews, and field notes were organized from August 01–October 01, 2023. The data analysis was done by OpenCode software and conventional content analysis was carried out following Colaizzi’s 7-step approach. Results In the study, four major themes and eighteen subthemes emerged, covering challenges encountered by nurse educators in Ethiopian public universities: challenges about educators themselves, nursing students, institutions/universities, problem-based learning strategies. Some specific points raised include lack of materials, negative student perceptions of problem-based learning, absence of standardized cases, and subjective assessments. Conclusion Nurse educators at public universities in Ethiopia faced challenges related to themselves, nursing students, their respective universities, problem-based learning cases, and assessment methods during problem-based learning implementation. Understanding these points provide further insights into the specific difficulties encountered by nurse educators concerning problem-based learning implementation.